Effects of drifts on scrape-off layer transport in W7-X. (1st February 2023) - Kriete, D.M.; Pandey, A.; Perseo, V.; Schmitt, J.C.; Ennis, D.A.; Gradic, D.; Hammond, K.C.; Jakubowski, M.; Killer, C.; König, R.; Maurer, D.A.; Reimold, F.; et al.
Abstract: Drifts affect particle, momentum, and energy transport in the scrape-off layer (SOL) of tokamaks and stellarators, altering plasma flows and creating asymmetries between divertors. To understand how drifts affect SOL transport in the W7-X island divertor, an experiment was performed to compare plasmas with matched core parameters but opposite magnetic field directions, and therefore opposite drift transport directions. Parallel flow measurements made with coherence imaging spectroscopy are interpreted with the aid of a diagnostic forward model and a 1D simple SOL model that includes the E × B drift. In low-density plasmas ( n ‾ e < 2 × 10 19 m −3 ), the poloidal E × B drift induces a large poloidal density asymmetry within the island SOL, as measured by divertor Langmuir probes. This in turn causes the parallel flow stagnation point to shift from the position halfway between targets to the X-point in the drift direction, leading to near-unidirectional flow throughout the SOL. As density increases, the effects of the poloidal E × B drift decrease substantially, resulting in a smaller density asymmetry and the development of a counter-streaming flow pattern. For the entire density range probed in this experiment ( n ‾ e = 1.5 − 6 × 10 19 m −3 ), the experimental observations are more consistent with the effects of the poloidal E × B drift than the radial E × B drift.